The usage and diagnostic yield of the implantable loop-recorder in detection of the mechanism of syncope and in guiding effective antiarrhythmic therapy in older people - BRIGNOLE, M; MENOZZI, C; MAGGI, R; SOLANO, A; DONATEO, P; BOTTONI, N; LOLLI, G; QUARTIERI, F; CROCI, F; ODDONE, D (Europace (London, England), 2005)
To evaluate the usage and diagnostic yield of the implantable loop-recorder (ILR) in detection of the mechanism of syncope and in guiding therapy in patients aged >/=65 years and comparing them with those <65 years. This was a two-hospital, observational, prospective study in consecutive patients with unexplained syncope who underwent an ILR implantation. Between November 1997 and December 2002, a total of 2052 patients with syncope were evaluated (local population of 590,000 inhabitants). The diagnosis remained unexplained in 371 (18%). Of these, 103 patients (5% of the total, 28% of those with unexplained syncope) received an ILR. There were 70 (76%) patients aged >/=65 years and 25 (24%) <65 years. ILR implantation was 110 and 9 per million inhabitants per year, respectively. During a mean follow-up of 14+/-10 months, syncope was recorded in 52 patients. Compared with younger patients those older had a 2.7 higher syncope recurrence rate (56% vs 32%, P=0.03); arrhythmias were 3.1 times more likely to be responsible for syncope (44% vs 20%, P=0.03). More patients >/=65 years finally received ILR-guided therapy (42% vs 20%, P=0.04). Among the 29 patients (25 of those >/=65 years) who received specific antiarrhythmic therapy, only one (3%), had recurrence of syncope during the subsequent follow-up of 40+/-18 months. In patients referred for investigation of unexplained syncope, the older subjects are more likely to have an indication for ILR implantation than those younger, ILR has a higher diagnostic value, an arrhythmia is more likely to be detected and successfully treated.